Modified group usability evaluation for non-immersive virtual reality (VR) system - Lau, Siew Yung; Chen, Chwen Jen (2009)
Usability testing plays an important role in system development. Conventionally, usability testing is often conducted with many individual participants. Cooperative usability testing, co-discovery, and remote usability testing are examples of usability testing techniques based on this individual approach. Recently, a group approach for usability testing, namely group usability testing was introduced. This approach involves several-to-many participants performing tasks simultaneously, with one to several testers observing and interacting with the participants. As such, group usability testing is able to produce a lot of useful data within a limited time. This paper discusses a modified version of a group usability testing and explains how it can be used to evaluate the usability of a non-immersive VR system. The proposed modified group approach aims to minimise the possibility of data loss during the usability evaluation process.